Understanding Types of Listening Skills Such as Intensive and Extensive - Khabibulloyevna, Azizova Dilafruz; qizi, Ergasheva Khulkaroy Rakhmatjon (Researchparks Publishing, 2023)
This article deals with the skills of differentiating types of listening. Using listening skills effectively during the lesson and the role of importance of them in the teaching-learning process was defined with real examples. The object of the research is the presenting information in a new and helpful manner so that students get a better understanding of what they are taught. Utilizing different kinds of listening methods in the classroom help learners to reach their aim. Learning a variety of helpful listening skills make the process of doing exercises efficiently and learning simple, interesting, and effective which makes it easier for the teacher to teach even the most difficult listening tasks. It also makes sense and saves time as students learn and understand the meaning very quickly by listening rather than reading.